2014
DOI: 10.1186/1129-2377-15-68
|View full text |Cite
|
Sign up to set email alerts
|

The role of headache chronicity among predictors contributing to quality of life in patients with migraine: a hospital-based study

Abstract: BackgroundHeadache chronicity has been known to elicit deleterious effects on quality of life (QOL). We evaluated the contribution of headache chronicity to QOL in relation to clinical, psychiatric, and psychosocial variables in patients with migraine.MethodsSubjects were recruited from a headache clinic and completed self-report questionnaires including the Migraine Disability Assessment (MIDAS), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), and Migraine-Specific Quality of Life (MSQoL). We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
47
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 35 publications
6
47
0
2
Order By: Relevance
“…The 36-Item Short Form Health Survey was used to quantify general health; the National ], and half of the patients had either constant or daily headaches. Even after successful treatment, many IIH patients develop chronic headaches [23], which can have a prolonged impact on QOL [24]. TVOs significantly impact vision-specific QOL [9 & ].…”
Section: Key Pointsmentioning
confidence: 99%
“…The 36-Item Short Form Health Survey was used to quantify general health; the National ], and half of the patients had either constant or daily headaches. Even after successful treatment, many IIH patients develop chronic headaches [23], which can have a prolonged impact on QOL [24]. TVOs significantly impact vision-specific QOL [9 & ].…”
Section: Key Pointsmentioning
confidence: 99%
“…Chronic migraine and chronic headaches associated with medication overuse are associated with worse QOL both directly and indirectly by worsening depression. 20 As is the case in patients with chronic migraine, 21,22 headache seems to be a direct significant contributor to lower QOL in patients with IIH. In fact, the HIT-6 score was associated with every SF-36 subscale.…”
mentioning
confidence: 91%
“…Several studies suggest that increases in depression and anxiety symptoms are associated with higher levels of migraine-related disability, [12][13][14] although only a few have evaluated these relationships in tertiary care headache centers. [15][16][17][18] Headache-related cognitions (catastrophizing) and beliefs (locus of control) are postulated to influence the development of chronic migraine, and migraine-related disability. A few studies have demonstrated relationships between higher pain catastrophizing and increased frequency and duration of migraine attacks, 19 higher intensity of headache pain, 20 and impairments in functioning and quality of life; 21 however, none of these studies evaluated people with migraine presenting for routine clinical care.…”
mentioning
confidence: 99%